Data Visualization on Global Warming by examining CO2 emissions - Nikolova, Dragana; Loshkovska, Suzana (Ss Cyril and Methodius University in Skopje, Faculty of Computer Science and Engineering, Republic of North Macedonia, 2023)
The continuous warming of the Earth's surface, the oceans and the atmosphere are part of global warming. The causes and effects of global warming are important to understand so that we can fight for the health of our planet. This paper uses relevant data and various visualizations to show how the temperature around the world changes and how carbon dioxide emissions affect that.
Keywords: visualization, global warming, Tableau